Training and teacher's skill improvement system and teacher's satisfaction on the existing training and development programs in the school - Sharmin, Nadia (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2018.